Historical Studies in the Physical Sciences. - McCormmach, Russell (Princeton legacy library., 2017)
This sixth volume of Historical Studies in the Physical Sciences presents articles by ten eminent scholars on the intellectual and social history of the physical sciences from the eighteenth century to the present. CONTENTS The Emergence of Japan's First Physicists: 1868-1900 (Kenkichiro Koizumi) The Reception of the Wave Theory of Light in Britain: A Case Study Illustrating the Role of Methodology in Scientific Debate (Geoffrey Cantor) Origins and Consolidation of Field Theory in Nineteenth Century Britain: From the Mechanical to the Electromagnetic View of Nature (Barbara Giusti Doran) Hertz's Researches on Electromagnetic Waves (Salvo D'Agostino) God and Nature: Priestley's Way of Rational Dissent (J.G. McEvoy and J.E. McGuire) Laurent, Gerhardt, and the Philosophy of Chemistry (John Hedley Brooke) The Lewis-Langrnuir Theory of Valence and the Chemical Community, 1920-1928 (Robert E. Kohler, Jr.) G.N. Lewis on Detailed Balancing, the Symmetry of Time, and the Nature of Light (Roger H. Stuewer) Rutherford and Recoil Atoms: The Metamorphosis and Success of a Once Stillborn Theory (Thaddeus J. Trenn) Originally published in 1976. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.